Impacto de la telefonía pública en la actividad rural: Proyecto Frontera Norte - Gallo, Mario (2003)
This study analyses and evaluates the results of public telephony services implementation efforts carried out by Osiptel in rural areas of extreme poverty. A specific project is chosen for this purpose, the Northern Border Project, whose completion three years ago allows accumulated information on its performance. Among the findings of the study is the increase in the use of public telephony, the predominance of incoming calls over outgoing calls, substantive differences in traffic volume only when revenue differences are important and business potential for operators. deprived of half a million dollars annually.